RETURN ON EQUITY, DEBT TO TOTAL ASSET RATIO, AND COMPANY VALUE - Rahmawati Hanny Yustrianthe; Sufyana Mahmudah (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2021)
This study aimed to determine the effect of Return on Equity (ROE) and Debt to Total Asset Ratio (DAR) on Firm Value in manufacturing companies listed on the Indonesia’s Stock Exchange 2015-2019, both partially and simultaneously. The research was categorized as an associative research by using. 179 companies listed on the Indonesia Stock Exchange (BEI) as a population. The sample obtained from 63 companies were selected using purposive sampling technique. The data in this study are secondary data obtained through the Indonesia Stock Exchange (BEI) and related company websites then being analyzed with multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression test, and normality test. The results showed that the Return on Equity (ROE) has a positive effect on Firm Value, Debt to Total Asset Ratio (DAR) has no significant effect on firm value, and Return on Equity (ROE) & Debt to Total Asset Ratio (DAR) has affect on firm value. Keywords: ROE, DAR, Book Value.